Uterine Carcinosarcomas: Clinical, Histopathologic and Immunohistochemical Characteristics. (September 2017) - Chen, Xiaowei; Arend, Rebecca; Hamele-Bena, Diane; Tergas, Ana I.; Hawver, Melanie; Tong, Guo-Xia; Wright, Thomas C.; Wright, Jason D.
Abstract : Carcinosarcomas (malignant mixed Müllerian tumors or MMMT) are rare malignant tumors in the female genital tract composed of both malignant epithelial and malignant mesenchymal components. They comprise <5% of all neoplasms in the gynecologic tract and have an aggressive clinical course. The purpose of this study is to evaluate the immunophenotype and possible histogenesis of carcinosarcomas of the uterus. Sixty-two cases of uterine carcinosarcomas diagnosed between 1995 and 2011 were retrieved from the gynecologic pathology files at Columbia University Medical Center. Representative tissue blocks containing both epithelial and mesenchymal components were selected from each case for histologic and immunohistochemical studies. Clinical data from each case were retrieved. The epithelial component was poorly differentiated adenocarcinoma in the majority (80.7%) of cases; in 17.7%, the carcinoma was moderately differentiated, and in only 1.6% the carcinoma was well differentiated. 53% of the tumors had homologous stromal elements and 47% displayed heterologous stromal elements. Immunohistochemical study revealed almost equal staining in both epithelial and mesenchymal components of carcinosarcomas for p16 and p53. PAX8 positivity was noted in 73% of epithelial components, but only 13% of stromal components, and PAX8 stromal positivity was never seen in the absence of PAX8 epithelial positivity. Expression of p16, p53, and PAX8 in both malignant components lends support to the monoclonal theory of uterine carcinosarcoma tumorigenesis. The roles of these tumor markers in the diagnosis and pathogenesis of this tumor and associations between clinical characteristics, tumor pathologic features, and prognosis are discussed. Abstract : Supplemental Digital Content is available in the text.